Chemical Analysis of Industrial Water - McCoy, James W. (Chemical Publishing Company, Incorporated, 1969)
Annotation This classic book has been reprinted by popular demand. Analytical chemists and chemical engineers will find this a well written and well illustrated treatise dealing with (and finding solutions to) the problems of water treatment, plant corrosion, and chemical analysis connected with the chemical process industries, steam and power plants and petroleum refining. This is an excellent manual for both laboratory and field workers.
Keywords: elektronické knihy; electronic books